Determination of Temperature Conditions for a Design of Engineering Constructions during a Fire - Petr Kucera; Jiri Pokorny (Communications - Scientific letters of the University of Zilina, 2011)
The problem of an engineering constructions design for effects of fire results from contemporary knowledge and procedures used in technical practice, however, is not limited only to norm recommendations, but looks also for other suitable methods of design. To examine fire endurance of engineering constructions by computation it is necessary to perform the determination of temperature in the area through models for follow-up thermal analysis. This article therefore presents principles of choice of appropriate design fire scenario by determination of the whole conception of safety and then presents a valiant solution of determination of the thermal action though the design fire by the form divergent from norm procedures. In addition, in the text it is alerted to deficiency and limitation in work used norm principles.